Differential Expressions of Protamine 1 (PRM1) and Protamine 2 (PRM2) Genes as Markers of Semen Quality in Pasundan Bulls - Santoso; A. Gunawan; C. Sumantri; R. I. Arifiantini; Herdis (Faculty of Animal Science, Bogor Agricultural University, 2022)
Several gene expressions are related to the success of spermatogenesis. Protamine plays an important role in sperm DNA packaging, spermatogenesis, and sperm quality. This study aimed to isolate RNA from spermatozoa and determine the gene expression profiles of protamine 1 (PRM1) and protamine 2 (PRM2). Six Pasundan bulls aged 5-8 years with a body weight of 380 kg-430 kg were used for this study. The Pasundan bulls were classified into group A (70%-79%) and group B (80%-89%) based on their sperm motility in fresh semen. In this study, correlation analysis was performed between fresh semen characteristics (volume, motility, concentration, abnormality, viability, intact plasma membrane (IPM), DNA integrity) and frozen semen characteristics after thawing (motility, viability, IPM, and DNA integrity). Total RNA was isolated from the frozen sperm pellet, and cDNA was synthesized. Specific PCR primers were used for the transcription of PRM1 and PRM2 from sperm. PRM1 and PRM2 gene expressions were evaluated by qRT-PCR, and ACTB was used as a control. The results showed that progressive sperm motility in the fresh sperm positively correlated with sperm viability and IPM. PRM1 and PRM2 were higher (p<0.05) in group B than in group A. This condition indicates the existence and influence of protamine on the parameters of progressive sperm motility. The expression of PRM1 and PRM2 genes could use as markers of semen quality in Pasundan bulls.